Infectious agents present in monk parakeet (Myiopsitta monachus) and rose-ringed parakeet (Psittacula krameri) invasive species in the parks of Madrid and Seville, Spain - López, Juan; Mogedas, María; Ballesteros, Carlos; Martín-Maldonado, Bárbara; Sacristán, Irene; García, Raúl; Ortiz, Juan Carlos; Esperón, Fernando (Frontiers in Veterinary Science, 2023)
Introduction The introduction of invasive species into an ecosystem could result in biodiversity loss and the spread of infectious agents that could cause re-emergent or emergent zoonotic diseases. Monk parakeets (Myiopsitta monachus) and rose-ringed parakeets (Psittacula krameri) are considered widespread invasive exotic species in urban habitats from the Iberian Peninsula. The aim of this study was to assess the presence of relevant infectious agents in wild parakeets captured in urban parks in Madrid and Seville (Spain). Methods A total of 81 cloacal samples were collected and analysed using molecular techniques. Results The prevalence of infectious agents varied between parakeet species: 9.5% of monk parakeets and 15% of rose-ringed parakeets were positive for enteropathogenic E. coli (EPEC), 13.3% of rose-ringed parakeets for avian influenza virus (AIV), 3.3% of rose-ringed parakeets for Newcastle disease virus (NDV), and a 23.8% of monk parakeets for Chlamydia psittaci. Discussion All C. psittaci-identified isolates were classified as B, E, or E/B genotypes, indicating transmission from wild urban pigeons to parakeets. These results highlight the need for monitoring parakeet populations due to the implications for human and animal health.